Further Training Needs for TVET Trainers: Lessons From a National Survey on Rwandan TVET Trainers’ Instructional Competencies - Kim, Woocheol; Shin, Heh Youn; Woo, Heajung; Kim, Jiyoung (Journal of Technical Education and Training, 2019)
Recently the Republic of Rwanda has expanded the national TVET system in response to the country’s growing need for a skilled youth population. However, policymakers have generally overlooked that the quality of the TVET system as a whole largely depends on the quality of TVET trainers. Recognising this lack, we conducted a national survey on TVET trainer’s instructional competencies to gather information about the current status of TVET trainers’ teaching quality. Additionally, after operating a pilot training program for TVET trainers at the RTTI, the national training institution for TVET trainers, we executed the same survey to the training participants to examine their instructional competencies. Then we compared its results in comparison to the results attained from the national survey. All assessments were done by measuring TVET trainers’ and students’ perceptions of TVET trainers’ teaching behaviors. This research represents the first efforts to understand the current level of TVET trainers’ teaching skills in Rwanda. Also, the survey results of the teaching behaviors of TVET trainers who received the training indicated the positive effect of the training. Implications of this research at the individual (trainers), institutional, and national levels are discussed at the end.